The delta neutrophil index predicts development of multiple organ dysfunction syndrome and 30-day mortality in trauma patients admitted to an intensive care unit: a retrospective analysis. Issue 1 (December 2018) - Kong, Taeyoung; Park, Yoo; Lee, Hye; Kim, Sinae; Lee, Jong; You, Je; Chung, Hyun; Park, Incheol; Chung, Sung
Abstract No studies have examined the role of delta neutrophil index (DNI) reflecting on immature granulocytes in determining the severity of multiple organ dysfunction (MODS) and short-term mortality. This study investigated the utility of the automatically calculated DNI as a prognostic marker of severity in trauma patients who were admitted to an intensive care unit (ICU). We retrospectively analysed prospective data of eligible patients. We investigated 366 patients. On multivariable logistic regression analysis, higher DNI values at 12 h (odds ratio [OR], 1.079; 95% confidence interval [CI]: 1.037–1.123;p < 0.001) and 24 h were strong independent predictors of MODS development. Multivariable Cox regression analysis revealed that increased DNI at 12 h (hazard ratio [HR], 1.051; 95% CI, 1.024–1.079;p < 0.001) was a strong independent predictor of short-term mortality. The increased predictability of MODS after trauma was closely associated with a DNI > 3.25% at 12 h (OR, 12.7; 95% CI: 6.12–26.35;p < 0.001). A cut-off of >5.3% at 12 h was significantly associated with an increased risk of 30-day mortality (HR, 18.111; 95% CI, 6.988–46.935;p < 0.001). The DNI is suitable for rapid and simple estimation of the severity of traumatic injury using an automated haematologic analyser without additional cost or time.